Pengembangan Evaluasi Pembelajaran Menggunakan Educandy Pada Materi Kekayaan Budaya Indonesia: Penelitian Research and Development pada Peserta Didik kelas IV di Sekolah Dasar Pertiwi Kota Bogor Semester Genap Tahun Ajaran 2024/2025 - Syifa Nur Azizah; Nita Karmila; Tatang Muhajang (STKIP Subang, 2025)
Development of Learning Evaluation Using Educandy on Indonesian Cultural Wealth Material. This research is an R&D (Research and Development) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which aims to develop Learning Evaluation Using Educandy on Indonesian Cultural Wealth material to determine its feasibility. This research was conducted at Pertiwi Elementary School, Bogor City with research subjects of 31 grade IV students in the even semester of the 2024/2025 school year. The validity test of this research was carried out by media experts, language experts and 2 material experts. To develop and perfect learning evaluation using Educandy, student and teacher responses are needed. The validation results by media experts are 100% with the criteria